Aplikasi Mobile Leskincare Pada Klinik Kecantikan dr. Lisni Elysah - Niken Aprilina; Hasdiana; Alkhowarizmi (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
The development of increasingly sophisticated beauty industry facilities and various beauty trends affectconsumers so that more and more people, especially women, go to beauty clinics to overcome their facial skinproblems. Beauty clinics have used technology and information to maintain a very tight business competitiotoday.To solve the above problem. Beauty clinic dr.Lisni Elysah needs an information system that can facilitatethe work of employees in the service system at the clinic. With increasing users of android smartphones, the authorchose to implement this system on the android platform. This system is made with several features that can bused, including registration, a list of consultation or maintenance schedules and also online product purchases.Making this system using android studio software, programming languages java and PHP and database usinMySQL. This research method uses the RAD (Rapid Application Development) method approach. The results othis study are to improve services and management from manual to computerized for clinics and as a servicefacility and information media for the community that has many features that can be used. The results of this studare based on the black box testing method that can be used as a well-designed application as expected.